2012
DOI: 10.1007/s00040-012-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of non-myrmecochorous plants by a “keystone disperser” ant in a Mediterranean habitat reveals asymmetric interdependence

Abstract: In contrast to other plant-animal mutualisms, seed dispersal interactions, and particularly seed dispersal by ants, are generally considered asymmetric, non-specialized relationships in which dispersers depend less on plants than vice versa. Although myrmecochory is well understood in many terrestrial ecosystems, dispersal of non-elaiosomebearing seeds by ants has barely been studied outside the Neotropics. Aphaenogaster senilis, a common ant in Southern Spain, collects a great variety of non-myrmecochorous di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Those keystone dispersers do not consume seeds (only the elaiosome), keep small colony size, frequently relocate their nest, forage solitarily, have excellent food detection capabilities and redisperse seeds beyond the nest limit (see Warren and Giladi (2014) for a detailed list). The large Cataglyphis species in our system (mainly C. savignyi and C. israelensis ) share many of the traits characterizing well-known keystone dispersers (Gorb and Gorb 1995; Boulay et al 2007 b ; Gove et al 2007; Barroso et al 2013; Leal et al 2014). Furthermore, the results from this study and our additional observations indicate that large Cataglyphis in our system disperse myrmecochorous seeds at high rates, to long distances (up to 40 m) and redisperse the seeds to favourite sites for plants establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Those keystone dispersers do not consume seeds (only the elaiosome), keep small colony size, frequently relocate their nest, forage solitarily, have excellent food detection capabilities and redisperse seeds beyond the nest limit (see Warren and Giladi (2014) for a detailed list). The large Cataglyphis species in our system (mainly C. savignyi and C. israelensis ) share many of the traits characterizing well-known keystone dispersers (Gorb and Gorb 1995; Boulay et al 2007 b ; Gove et al 2007; Barroso et al 2013; Leal et al 2014). Furthermore, the results from this study and our additional observations indicate that large Cataglyphis in our system disperse myrmecochorous seeds at high rates, to long distances (up to 40 m) and redisperse the seeds to favourite sites for plants establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Like the previous species, A. senilis also appeared in very small numbers, in winter, spring and summer and in several stages of decomposition. The individual way the workers of this species carry their forage activity [ 50 ] may explain this reduced number of collected specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies often move their nests to open areas in the spring and autumn and to shady areas in the summer. Workers are individual foragers moving quickly [ 50 ]. They are omnivores feeding on both seeds and animal remains.…”
Section: Discussionmentioning
confidence: 99%
“…Ants were never observed carrying seeds out of the trays nor we detected any sign of rodent presence. Previous studies have found a negligible effect of ants on the removal of P. lentiscus seeds (Aronne & Wilcock 1994;Barroso et al 2013). The effect of seed predators may be expected to be larger under shrub patches where more seeds and noningested fruits accumulate, which should attract more seed predators (Alcántara et al 2000).…”
Section: Discussionmentioning
confidence: 95%